Critical defining characteristics for nursing diagnosis about ineffective breastfeeding - Sandra Cristina de Alvarenga; Denise Silveira de Castro; Franciéle Marabotti Costa Leite; Telma Ribeiro Garcia; Marcos Antônio Gomes Brandão; Cândida Caniçali Primo
ABSTRACT Objective: To investigate the Nursing diagnostic accuracy measures and to propose a model to use defining characteristics in order to judge the nursing diagnosis of ineffective breastfeeding. Method: Cross-sectional study with a sample of 73 binomials mom-child hospitalized in a maternity ward of an University Hospital, from July to August of 2014. Results: The diagnostic predominance rate was 58.9%. The characteristics that best meet the needs of logistic regression model were: discontinuance of breast sucking; infant's inability of seizing the areola-nipple region correctly; infant's crying one hour after breastfeeding and inappropriate milk supply perceived. Conclusion: Breastfeeding process is dynamic; diagnostic judgement may suffer some changes according to the time data are collected; the defining characteristics are the best predictors if associated with models and rules of use.